Analisis kesalahan pengucapan kosakata bahasa Indonesia oleh pemelajar BIPA tingkat dasar di INCULS UGM Yogyakarta - Salahuddin Salahuddin (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
In order to improve the level of Indonesian as an international language, the Indonesian government's Language Agency has provided Indonesian language learning institutions in various countries, including domestically. At several large universities such as Gadjah Mada University, Indonesian language training is given to foreign students who continue their studies at various faculties at UGM Yogyakarta. This study aims to observe the pronunciation ability of Indonesian vocabulary by BIPA students who study at a basic level in INCULS UGM. This research used a descriptive qualitative approach. There were 5 foreign students involved as respondents which were two foreign students from Pakistan, and three other foreign students from Yemen, Jordan, and Ethiopia. The research was conducted by providing a list of 15 Indonesian vocabularies containing the object of research, such as vocabulary containing the phoneme /ŋ/, /ñ/, distinguishing the phoneme /e/ and its allophone variations, as well as various types of diphthongs. The result shows that there are misunderstandings in the form of adding the phoneme /y/ after the phonemes /ŋ/ and /ñ/, omitting one of the phonemes in the diphthong phonemes, and alternately exchanging the pronunciation of the phonemes /e/ and /ə/ in each position in Indonesian. The errors happen due to their lack of ability to distinguish the phonemes found in Indonesian from the phonemes in the foreign student's mother tongue. By conducting this research, it is expected to be helpful for educators to make decisions about the content of teaching materials, or even further for other researchers who want to pursue a better research design and result